Dynamic evaluation of toe–heel and medio-lateral load distribution and hoof landing patterns in sound, unshod Standardbred horses with toed-in, toed-out and normal hoof conformation. (February 2021) - Mokry, A.; Van de Water, E.; Politiek, H.T.; van Doorn, D.A.; Pille, F.; Oosterlinck, M.
Highlights: A flat hoof landing predominated over all hoof conformations in sound Standardbreds. There was no significant association between hoof conformation and landing pattern. When walking, toed-out horses presented higher medial loading at the end of stance. Mild deviations in hoof conformation did not affect dynamic load distribution. Abstract: Dynamic load distribution and landing patterns play an important role in equine orthopaedics. The aim of this study was to analyse dynamic load distribution and hoof landing patterns of sound Standardbreds. Twenty-four sound, unshod Standardbreds were walked and trotted over a pressure plate to obtain the peak vertical force (PVF), vertical impulse (VI) and stance time (ST) of both forelimbs. Asymmetry indices between both forelimbs were calculated and the dynamic medio-lateral and toe–heel load distribution of the forelimbs were compared between normal, toed-in and toed-out horses. The hoof landing patterns were determined on the first loaded zone. Linear mixed models and Chi-square analysis were used for statistical analysis ( α = 0.05). At walk and trot, there were no significant differences in asymmetry of PVF, VI and ST between normal ( n = 9/24 horses), toed-in ( n = 6/24 horses), and toed-out horses ( n = 9/24 horses). In both forelimbs, a flat landing (39.6% and 70.8% at walk and trot, respectively) predominated over all hoof conformations. No significant association between hoof conformation and landing pattern was observed ( P > 0.05). Toed-out horses had significantly higher loading of the medial zone at the end of the stance phase at walk than normal horses ( P = 0.002). No other statistically significant differences in load distribution were observed ( P > 0.05). In conclusion, flat landing was more common in Standardbred horses than previously described in Warmbloods, emphasising the need for breed-specific clinical reference data and biomechanical studies. Moreover, mild deviations in hoof conformation did not necessarily affect load distribution.